Analisis Usaha Pembibitan Pinang Batara di Lahan Gambut Tanjung Jabung Barat Provinsi Jambi - Nur Imdah Minsyah; Firdaus Firdaus (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Minsyah NI, Firdaus F. 2019. Business analysis of seeds areca nut batara on Peatlands Tanjung Jabung Barat District Jambi Provinci. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 576-583. Palembang: Unsri Press. Batara Areca nut, is the first superior variety of areca nut in Indonesia, released by the Minister of Agriculture through Minister of Agriculture Decree Number: 199/Kpts/ SR.120/1/2013. Demand for seedlings continues to increase, from several provinces.This momentum is used by some farmers to breed Pinang Batara seeds. The aim of this study to describe: profile, seeds business, and profits earned by the breeder. The data used are primary data, secondary data and other relevant information.Areca nut breeding seedlingsprovide adequate benefits and feasible to continues. With a capital of Rp. 4.598 million/2000 seeds, for 6 months, the profit gained was Rp. 8,902 million, the value of R/C and B/C ratio to reach 2.97 and 1.97. Seedlings sold by breeders are grouped in: 1). Type A, which is a prospective seed in the form of a dark red round areca nut; 2). Type B, is the seed that has germinated, and; 3). Type C, is the seeds ready for planting.Keywords: batara areca nut, seeding, seed type, and superior varieties